PENGARUH CITRA, KUALITAS LAYANAN, PROMOSI DAN PERSEPSI HARGA DALAM MEMPENGARUHI KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Studi pada pelanggan Carrefour Semarang) - Herry Suharyanto, 11.42.02.0022 (Students Journal of Economic and Management, 2013)
The purpose of this study was to analyze the image, quality of service, promotion, price perceptions have a positive effect on the creation of customer satisfaction and to analyze the creation of customer satisfaction has a positive effect on customer loyalty.Â The object of this study is Carrefour customers in Semarang research method using SPSS analysis requires that a representative sample to be used in other research. Regression analysis equations I know the coefficient of determination or R ajusted 0.647. This means that the effect of the independent variable is the image, quality of service, promotion, price perception and satisfaction on customer loyalty is equal to 64.7% or in other words, changes in customer loyalty variation can be explained by the image, quality of service, promotion, price perception with 64, 7%, while 35.3% is influenced by other variables not examined. The results of the analysis of the variable image, quality of service, promotion, price perception, customer satisfaction and customer loyalty shows that image, quality of service, promotion, price perception and customer satisfaction has a positive and significant impact on customer loyalty variables, shows that the higher the effect of each each independent variable is the image, quality of service, promotion, price perception and customer satisfaction, the customer will be more loyal. Keywords: Image,Quality service, Promotion, Perceived price, customer satisfaction and customer loyalty.